2012
DOI: 10.1159/000342669
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam versus Carbamazepine in Patients with Late Poststroke Seizures: A Multicenter Prospective Randomized Open-Label Study (EpIC Project)

Abstract: Background: Strokes are the leading cause of epileptic seizures in adults and account for 50% of seizures in those over the age of 65 years. The use of antiepileptic drugs to prevent recurrent poststroke seizures is recommended. Methods: One hundred and twenty-eight patients with poststroke seizures were randomly allocated to treatment with either levetiracetam (LEV) or sustained-release carbamazepine (CBZ) in a multicenter randomized open-label study. After a titration study phase (2 weeks), the optimal indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 60 publications
11
102
1
2
Order By: Relevance
“…Attention deficit, frontal executive function, and functional scales were significantly worse in the carbamazepine group. Premature discontinuation due to serious adverse effects was not statistically significant between the groups [35]. In a smaller study, 64 patients presenting with the first (early or late) poststroke seizure received lamotrigine or carbamazepine in a randomized 1:1 ratio.…”
Section: Treatmentmentioning
confidence: 88%
See 3 more Smart Citations
“…Attention deficit, frontal executive function, and functional scales were significantly worse in the carbamazepine group. Premature discontinuation due to serious adverse effects was not statistically significant between the groups [35]. In a smaller study, 64 patients presenting with the first (early or late) poststroke seizure received lamotrigine or carbamazepine in a randomized 1:1 ratio.…”
Section: Treatmentmentioning
confidence: 88%
“…The authors concluded that gabapentin was safe and useful for poststroke seizures [48]. Other authors randomized 106 patients with late poststroke seizures to levetiracetam or sustained-release carbamazepine [35]. No statistically significant difference in the number of seizure-free patients was found between the two groups.…”
Section: Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…No randomized clinical trials have explored the evaluation of older versus newer AEDs in stroke-related epilepsy. However, the newer agents offer the advantage of fewer side effects, which makes them appropriate to use particularly in the elderly [14,15,35]. A few studies have shown gabapentin and lamotrigine to be effective in the treatment of late-onset poststroke seizures [16,17].…”
Section: Managementmentioning
confidence: 99%